Changes in blood markers of serotoninergic activity following high intensity cycle ergometer exercise - Baker, J. S.; Morgan, R.; Hullin, D.; Castell, L. M.; Bailey, D. M.; Davies, B. (Research in Sports Medicine, 2006)
The purpose of this study was to measure concentrations of adrenaline (A), noradrenaline (NE), free tryptophan (f-Trp), prolactin (PRL), nonesterified fatty acids (NEFA), and blood lactate following 30 s of high-intensity cycle ergometer exercise. Adrenaline (A) and NE concentrations increased immediately postexercise (P < 0.05) and returned to levels observed at baseline 24 h later. Plasma f-Trp concentration decreased by 23.5% immediately following exercise (P < 0.05). There were no changes observed in serum concentrations of PRL. Plasma NEFA concentrations decreased immediately following exercise by 46% (P < 0.05) and returned to baseline values 24 h later. Whole blood lactate concentrations increased immediately post exercise (P < 0.05), and were higher than those measured 24 h later (P < 0.05). These findings indicate that blood markers of serotoninergic activity were unaltered by a single 30 s bout of maximal cycling.